Developing a tracking system for a robot water - Muhamad Qabul Fared Bin Abdull Rahim (2023)
This thesis represents the study and research experiment on developing a tracking system for a robot waiter. By using Arduino programming to program and design the codes, it will help the robot to move around and follow the desired outputs that is needed. The objective of this thesis is to develop and compare the motion that is used for this robot waiter that can send and collect object at a desired location and also to develop a suitable coding program using Arduino programming to be applied by the robot waiter. The parameters that have been considered during this experiment is the speed movements of the robots, the responsive time of the robot and also whether or not the robot could move steadily. The result of this project shows how far the robot could move and how efficient the programming code.